1982
DOI: 10.1071/ar9820131
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a concurrent infection of Trichostrongylus colubriformis on the productivity and physiological and metabolic responses of lambs infected with Ostertagia circumcincta

Abstract: Weaner lambs were infected for 16 weeks with 900 or 3000 Trichostrongylus colubriformis larvaelweek alone, with 38 000 Ostertagia circumcincta larvaelweek alone, or with the two parasites concurrently at these dose levels. Concurrent infections with T. colubrifovmis, which when given alone had no significant effect, reduced liveweight gain by 15 kg over the 16-week infection period compared with a 6-kg reduction in liveweight of lambs infected with O. civcumcincta alone. T. colubvifovmis when given alone did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1
1

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(31 citation statements)
references
References 0 publications
2
26
1
1
Order By: Relevance
“…Parasitic infection has increased the rates of synthesis of hepatic constitutive proteins Bermingham et al 2006). The 4% decrease (P < 0.15) in skin FSR I observed in the current study is consistent with previous studies in parasitized sheep (Symons and Jones 1975;Steel et al 1980Steel et al , 1982. Whilst these studies have shown decreased skeletal muscle protein synthesis during parasitic infection, similar infection protocols to the current study showed that an adult T. colubriformis infection did not affect the FSR of the biceps femoris (Bermingham et al 2006).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Parasitic infection has increased the rates of synthesis of hepatic constitutive proteins Bermingham et al 2006). The 4% decrease (P < 0.15) in skin FSR I observed in the current study is consistent with previous studies in parasitized sheep (Symons and Jones 1975;Steel et al 1980Steel et al , 1982. Whilst these studies have shown decreased skeletal muscle protein synthesis during parasitic infection, similar infection protocols to the current study showed that an adult T. colubriformis infection did not affect the FSR of the biceps femoris (Bermingham et al 2006).…”
Section: Discussionsupporting
confidence: 92%
“…Trichostrongylus colubriformis, the major sheep parasite in New Zealand, imposes a severe financial cost on farmers, due in part to its negative effects on liveweight gain (van Houtert et al 1995) and wool production (Steel et al 1980(Steel et al , 1982. Protein is the major constituent of muscle and wool.…”
Section: Mots Clés: Infection Parasitaire Synthèse Protéique Agneauxmentioning
confidence: 99%
“…circumcincta live in the abomasum of sheep, whereas T. colubriformis is an inhabitant of the small intestine. Under laboratory conditions, a dose-dependent synergistic effect has been described for concurrent infections with these species (Dobson et al, 1992;Steel et al, 1982;Sykes et al, 1988). When sheep were infected with high doses of both worms, their adult worm burdens and weight loss exceeded those expected from single species infections.…”
Section: Co-infectionmentioning
confidence: 99%
“…(17%), compared with 6 and 67%, respectively, in Steel et al's (1984) study. Steel et al (1982) showed that, compared with Trichostrongylus, considerably higher infections of Ostertagia can be tolerated before animal production is affected, and Haemonchus contortus is recognised as being considerably more pathogenic than either of them. That Barger & Southcott's (1978) lambs were set stocked on the sheep system but rotationally grazed on the sheep and cattle system may have also contributed to differences between their systems, as it has been conjectured that, compared with rotational grazing, set stocking increases nematode intake of lambs.…”
Section: Discussionmentioning
confidence: 99%